2020
DOI: 10.1371/journal.ppat.1008206
|View full text |Cite
|
Sign up to set email alerts
|

Stress keratin 17 enhances papillomavirus infection-induced disease by downregulating T cell recruitment

Abstract: High-risk human papillomaviruses (HPVs) cause 5% of human cancers. Despite the availability of HPV vaccines, there remains a strong urgency to find ways to treat persistent HPV infections, as current HPV vaccines are not therapeutic for individuals already infected. We used a mouse papillomavirus infection model to characterize virus-host interactions. We found that mouse papillomavirus (MmuPV1) suppresses host immune responses via overexpression of stress keratins. In mice deficient for stress keratin K17 (K1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 66 publications
7
38
0
Order By: Relevance
“…These carcinomas express markers of MmuPV1 infections and biomarkers commonly found in HPV-associated cancers. We also observed upregulated levels of cytokeratin 17 in MmuPV1-induced oral tumors, a host gene recently identified to mediate papillomavirus-induced immunosuppression (26). We extended our studies to genetically immunocompetent FVB mice and found that MmuPV1 also infects the tongue.…”
supporting
confidence: 64%
See 3 more Smart Citations
“…These carcinomas express markers of MmuPV1 infections and biomarkers commonly found in HPV-associated cancers. We also observed upregulated levels of cytokeratin 17 in MmuPV1-induced oral tumors, a host gene recently identified to mediate papillomavirus-induced immunosuppression (26). We extended our studies to genetically immunocompetent FVB mice and found that MmuPV1 also infects the tongue.…”
supporting
confidence: 64%
“…Our laboratory recently discovered that stress cytokeratin 17 is one of the most upregulated host genes upon cutaneous MmuPV1 infection and that K17 plays an important role in mediating the ability of the virus to evade immune clearance and establish persistent disease (26). We observed that K17 is also upregulated in the context of MmuPV1-infected tongue lesions ( Fig.…”
Section: Development Of An Mmupv1 Oral Infection Model In Immunodeficmentioning
confidence: 64%
See 2 more Smart Citations
“…Keratin 6B ( KRT6B ) is a type II cytokeratin, which is an important biomarker for lung adenocarcinoma [ 40 ]. These genes are known as virus-induced host factors that control the recruitment of T-cells and correlate with chronic virus infections [ 41 ]. In addition, the tumor necrosis factor, alpha-induced protein 3 ( TNFAIP3 ), is a central regulator of immunopathology and is associated with the maintenance of immune homeostasis and severe viral infections [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%